الادارة الالكترونية في شركات التأمين: إنموذج مقترح في شركة التأمين العراقية العامة (Journal of Accounting and Financial Studies ( JAFS ), 2014)
In recent decades, the world has faced some rapid technical developments, affected on many fields of life, which had the best chance in the information and communication technology, such that it created an entirely new situation, summed up the life and development of business enterprises. This is while these developments have changed a lot the reputation of management institutions and civil society organizations in return. In addition, they have linked the citizen and those institutions in their different specialties within a distinct electronic format called e-management in the contemporary literature.    This study attempted to highlight the importance of investment in building e-management by linking citizens, management institutions and insurance companies using a standard electronic pattern, which provides different transactions easily, with economical effort and considerable money and time.In addition, this study tried to achieve several goals, focusing on the diagnosis of the current reality of insurance dealings in Iraq, and its most important disadvantages, by applying a sample of e-business representing the e-management. Also, the insurance company of Iraq was selected as an the application field, through the case study of this company as a scientific method, including a proposal to apply the e-management based on a certain questionnaire, for the purpose of benefiting from its results’ analysis in support of the application of e-management.